SOME INTERPRETATIONS OF HUMAN CONSTRUCTION IN THE PHILOSOPHY OF SIGMUND FREUD AND ERICH FROMMc (Scientific journal of the Fergana State University, 2023)
The article analyzes socio-philosophical issues of human destruction, its social consequences, aspects that destroy civilizations. Based on the works of German philosophers Z. Freud and E. Fromm, the dialectical nature of human destruction and its specific features is studied. The role of the principle of destruction in the conflict between existing reality and events in human history is also analyzed.